A New Journal’s Fifth Anniversary: Problemy Ekorozwoju/Problems of Sustainable Development - Cao, Yucheng (Problemy Ekorozwoju, 2011)
Publishing a new journal for five years is not a long time. However, it is long enough to evaluate the role which the journal plays in disseminating knowledge on sustainable development. According to the Thomson Scientific Master Journal List (Lista Filadelfijska) the journal entitled Problemy Ekorozwoju (Problems of Sustainable Development) appears at the top of the list.